Interpretasi Poligami dalam Qs. Al-Nisa’ Ayat 3 dan 129: Studi Perbandingan antara Penafsiran Muhammad Syahrur dan Muhammad Abduh - Fauzi Fathur Rosi; Daafiqin Syaqiq Maulana (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2023)
Polygamy is one of the controversial issues whose debates have spawned various opinions, especially according to Muhammad Syahrur and Muhammad Abduh, these two figures depart from different cultural backgrounds even though they are both in contemporary times. This study discusses the interpretation of polygamy in QS. al-Nisa' verses 3 and 129 according to Muhammad Syahrur and Muhammad Abduh. The purpose of this study is to analyze how the interpretation of Muhammad Syahrur and Muhammad Abduh along with the differences and similarities about polygamy in QS. al-Nisa' verses 3 and 129. This research uses a literature review with a qualitative approach with comparative descriptive analysis techniques. The results of this study show that Muhammad Syahrur allowed polygamy with qualification conditions in terms of quality, namely the status of widows who have children applies to second, third or fourth wives. And Muhammad Abduh allowed polygamy on the condition that in case of emergency, i.e. if the maslahat is more than the mudarat. The two have different conditions when it comes to polygamy. Muhammad Syahrur requires in terms of quality and Muhammad Abduh forbids on the grounds of justice. In terms of quantity, there is no difference between the two.